Efficacy and Safety of Dual Antiplatelet Therapy in Patients Undergoing Coronary Stent Implantation: A Systematic Review and Network Meta-Analysis - Yi Xu; Yimin Shen; Delong Chen; Pengfei Zhao; Jun Jiang (Journal of Interventional Cardiology)
Introduction. This network meta-analysis aimed to evaluate the efficacy and safety of different dual antiplatelet therapies (DAPTs) after percutaneous coronary intervention (PCI) with drug-eluting stents (DESs). Methods. Randomized controlled trials (RCTs) comparing longer-term (>12 months) DAPT (L-DAPT), 12-month DAPT (DAPT 12Mo), 6-month DAPT (DAPT 6Mo), 3-month DAPT followed by aspirin monotherapy (DAPT 3Mo + ASA), 3-month DAPT followed by a P2Y12 receptor inhibitor monotherapy (DAPT 3Mo + P2Y12), or 1-month DAPT with a P2Y12 receptor inhibitor monotherapy (DAPT 1Mo + P2Y12) were searched. Primary endpoints were all-cause mortality, cardiac death, myocardial infarction (MI), major bleeding, any bleeding, definite or probable stent thrombosis (ST), and net adverse clinical events (NACE). This Bayesian network meta-analysis was performed with the random-effects model. Results. Twenty-four RCTs (n = 81339) were included. In comparison with L-DAPT, DAPT 6Mo (OR: 0.50, 95% CI: 0.29–0.83), DAPT 3Mo + P2Y12 (OR: 0.38, 95% CI: 0.18–0.82), DAPT 3Mo + ASA (OR: 0.44, 95% CI: 0.17–0.98), and DAPT 1Mo + P2Y12 (OR: 0.45, 95% CI: 0.14–0.93) were associated with a lower risk of major bleeding. DAPT 3Mo + P2Y12 (OR: 0.58, 95% CI: 0.38–0.88) reduced the risk of any bleeding when compared with DAPT 12Mo. L-DAPT decreased the risk of MI and definite or probable stent ST when compared with DAPT 6Mo. DAPT 3Mo + P2Y12 decreased the risk of NACE in comparison with DAPT 6Mo and DAPT 12Mo. No significant difference in all-cause mortality and cardiac death was observed. In patients with acute coronary syndrome, DAPT 6Mo was comparable to DAPT 12Mo. Conclusion. Short-term (1–3 months) DAPT is noninferior to DAPT 6Mo after DESs implantation, while L-DAPT reduces MI and definite or probable ST rates. DAPT 3Mo + P2Y12 might be a reasonable trade-off in patients with high risk of bleeding accompanied by ischemia.